Effect of positioning errors of frames on fuselage panel assembly deformation. (May 2016) - Yan, Weimiao; Bi, Yunbo; Qiao, Mingjie
In aircraft assembly, frames are usually used as the skeleton shape benchmarks of a fuselage panel to locate other parts accurately, thereby coordinating the relative position relationships between each part. In order to guarantee the assembly quality, a methodology for analyzing the effect of positioning errors of frames on fuselage panel assembly deformation is proposed. A finite element model of the fuselage panel is established first and then a mathematical model for representing the assembly deformation is derived. To contain more assembly deformation information, the optimal measurement point placement method is adopted to extract a set of finite element nodes as the measurement point locations from a large candidate set. Meanwhile, the mathematical relationship between the position errors of measurement points and the positioning errors of frames is also determined, which is then combined with the Monte Carlo simulation and the grey relational analysis to quantitatively analyze the impacts of the positioning error(s) generated by single or multiple frames on fuselage panel assembly deformation.